Effect of biodegradable and nanotropic fertilizers (Manganese, Cupper, and Zinc) on economic yield, antioxidant enzymes and concentration of some elements in Roselle (Hibiscus sabdariffa L.) under drought Stress - esmat hashemi; nafiseh mahdi nezhad; barat ali fakheri; roghaei mohammadpour (فیزیولوژی محیطی گیاهی, 2018)
In order to investigate the effects of nanofertilizers (Fe, Zn, and Mn), Bioumik biological fertilizer, and drought stress on the economic yield of the sepal, antioxidant enzymes, and concentration of some elements in roselle plants under drought stress, a spilt plots experiment was conducted in a randomized complete block design with three replications at Research Farm of the University of Zabol in 2015. Experimental treatments included drought stress at 4 levels (30, 50, 70, and 90 percent available moisture) as the main factor and four levels of fertilizers (no fertilizer, nano-iron, iron compounds, and nano-biological fertilizers) as the sub-agent. The main effects of drought stress, fertilizer, and their interactions on all traits were significant at P≤0.01. The highest fresh and dry weights were obtained under nano-iron fertilizer and 70 percent drought tolerance. Nano-iron fertilizer and 30 percent available moisture content resulted in the highest levels of catalase, guaiacol peroxidase, and ascorbate peroxidase enzymes. Application of nano-iron fertilizer increased the concentration of micro and macro elements (Fe, Zn, Nitrogen, Phosphorus, and Potassium) in the plant and the highest concentrations of the elements were observed in the interaction of nano-iron fertilizer with drought stress at 70 percent capacity of the pot. In general, it can be said that stress has a destructive effect on the plant, the use of nano-iron increases plant tolerance to stress, and the use of Roselle plant is suitable for stress conditions.